2018
DOI: 10.1177/0093854818790291
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Debt During the Prisoner Reintegration Process: Who Has It and How Much?

Abstract: Much recent, national attention has centered on financial sanctions and associated debt burdens related to criminal justice. Scholars and practitioners alike have argued that financial debt among the incarcerated, in particular, exacerbates a transition home already defined by difficulties. This article takes a step back and assesses who is at risk of these adverse consequences in reentry by examining the extent of debt burdens that resulted from financial sanctions, its sources, and the individual-level facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…Prison administration could also consider measures that reduce barriers to medical treatment. For example, it has become typical for many criminal justice‐related fees and costs to be shifted to defendants or prisoners (Harris, ; Link, ), and this includes medical co‐payments for treatment (Bannon, Nagrecha, & Diller, ). Although a co‐pay may be affordable for those outside the walls, it may prevent access to treatment among the incarcerated who may make far less than minimum wage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prison administration could also consider measures that reduce barriers to medical treatment. For example, it has become typical for many criminal justice‐related fees and costs to be shifted to defendants or prisoners (Harris, ; Link, ), and this includes medical co‐payments for treatment (Bannon, Nagrecha, & Diller, ). Although a co‐pay may be affordable for those outside the walls, it may prevent access to treatment among the incarcerated who may make far less than minimum wage.…”
Section: Discussionmentioning
confidence: 99%
“…Economic hardship, on the other hand, is a well‐documented source of strain that can increase the likelihood of engaging in criminal behavior to achieve economic goals (Agnew, ; Stogner & Gibson, ) or of coping in a violent manner as a result of the frustration with living in deprivation. The strain associated with financial difficulty has led to a growth in research aimed at examining the prevalence of financial sanctions, debt, and mounting economic hardship among former prisoners (Link, ; Link & Roman, ; Martin, Sykes, Shannon, Edwards, & Harris, ; Roman & Link, ). In light of the financial difficulties faced, unemployment and an increase in economic hardship are both expected to increase the probability of reoffending after release from prison…”
Section: Role Of Employment Family Conflict and Financial Problems mentioning
confidence: 99%
“…Studies of all types found that between 50 and 90% of people with LFOs are in arrears (Arditti & Few, 2006 ; Diller, Greene, & Jacob, 2009 ; Harris et al, 2010 ; Link, 2019 ; Nagrecha, Katzenstein, & Davis, 2015 ; Pleggenkuhle, 2018 ), other than one mixed methods study which found that only 20% have LFO and/or child support debt (La Vigne, Visher, & Castro, 2004 ). African-Americans are more likely to owe LFO debt (Link, 2019 ). LFO debt is most often reported as arising from post-release supervision fees including half-way housing rent (Diller et al, 2009 ; Johnson, 2015 ; Link, 2019 ; Ortiz & Jackey, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…African-Americans are more likely to owe LFO debt (Link, 2019 ). LFO debt is most often reported as arising from post-release supervision fees including half-way housing rent (Diller et al, 2009 ; Johnson, 2015 ; Link, 2019 ; Ortiz & Jackey, 2019 ). LFO debts can cause long term debt and damaged credit (Harris et al, 2010 ; Pleggenkuhle, 2018 ), with one study reporting 75% sent to collections; African-Americans are more likely to have their debt sent to collections (Diller et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation